Emphysematous pyelonephritis: Case report and literature overview. Issue 3 (August 2018) - Ziegelmüller, Brigitte Katharina; Szabados, Bernadett; Spek, Annabel; Casuscelli, Jozefina; Stief, Christian; Staehler, Michael
Introduction: Emphysematous pyelonephritis is a rare necrotizing infection of the kidney with a poor prognosis. If it occurs in patients with a reduced general condition, this infection is life threatening. Early diagnosis is made by computed tomography. Treatment options are drainage and intensive care or immediate nephrectomy in severe cases. Case description: A 73-year-old woman in a poor general condition presented with a fulminant urosepsis. Computed tomography revealed an impressive abscess formation of the right kidney with free air retro and intraperitoneal. The diagnosis of emphysematous pyelonephritis was made. Besides septicemia, she had a multiorgan failure including kidney and liver function deterioration. Nephrectomy was performed immediately. The postoperative course was successful with a complete stabilization of the kidney and liver function and reconvalescence of the patient. Discussion: The widespread availability of imaging techniques leads to early diagnosis and a reduction of mortality of renal and periphrenic abscesses and even of emphysematous pyelonephritis. However, severe cases have a poor outcome and require aggressive and immediate therapy. Besides systemic antibiotic therapy and percutaneous and surgical drainage, radical nephrectomy is a viable therapy option and should be performed immediately in patients with several risk factors, poor prognosis, and extensive findings. Conclusion: Radical nephrectomy being performed immediately seems to be the optimal management in patients with acute emphysematous nephritis and urosepsis.